Prevalencia de sobrepeso y obesidad en trabajadores del Gobierno Autónomo Descentralizado del Cantón Tulcán - Calapaqui De La Cruz, Katherine Nayely (2024)
The prevalence of overweight and obesity in workers of the Decentralized Autonomous Government in the canton Tulcan is a significant concern given that both obesity and overweight are considered health problems worldwide, caused by diverse factors such as poor nutrition, sedentarism, and socioeconomic conditions. The general objective is to determine the prevalence of overweight and obesity in the Decentralized Autonomous Government workers in the canton Tulcan. The methodology applied was the quantitative approach supported by theoretical methods such as inductive-deductive, historic-logic, analytic-synthetic and systemic approach; in addition, the instrument of research was the questionnaire applied to the workers mentioned above. The current diagnosis regarding the Decentralized Autonomous Government in the canton Tulcan allowed to determine the relevance of the problem, showing the following results: 62% of the population considered that they are overweighted, 75% of the population claimed that their working style directly affects in their weight, 85% claimed not to do any sport or physical activity; these data was essential to carry on with the research, so that to develop educational strategies addressed to raise awareness among the workers regarding the serious complications associated to overweight and obesity. These strategies included a nutritional program as well as the promotion of physical activities. The validation of the proposal was made by the analysis of the results obtained, evaluating, in this way, the effectiveness of the interventions and regulating the strategies to guarantee a significant and consecutive improvement in the worker’s health. This comprehensive approach aims not only to address the current problem but also prevent upcoming complications in the health area.